Environmental flow assessment for energy generation sustainability employing different hydraulic evaluation methods: Cambasi hydropower plant case study in Turkey - Karakoyun, Yakup; Yumurtaci, Zehra; Donmez, Aydin Haci (SPRINGER, 2016)
The operating principle of hydroelectric power plants (HPP) is based on utilizing the potential energy of water, which constitutes the basic component of the plant. In other words, water is crucially important in energy production in hydroelectric power plants. The importance of water is not only limited to the energy production, but also can affect directly or indirectly all living things in the water basin. This study deals with the methods of determining the environmental flow, which will not damage the integrity of the rivers and the ecosystem in HPPs, together with enabling the sustainable electricity production as an indirect result. Suggestions are made for determining the environmental flow for CambasA +/- regulator and Hydropower plant, a run-of-river type power plant in Turkey, after reviewing commonly used methods all over the world. Tennant, Tessmann, and flow duration curve methods were used in determining the environmental flow. Separate calculations were carried out for CambasA +/- and Ogene regulators, which constitute the hydropower plant. The calculated values were compared with the normal (regime) flow rates and project flow values. As a result, Tessmann method, one of the hydrological based environmental flow determination methods, and good category of Tennant method, 20 % of annual average flow in dry period and 40 % of annual average flow in wet period, are proposed for CambaAYA +/- HPP.
Keywords: Environmental flow; Environmental impact assessment; Hydroelectric power plant; Hydraulic power; Ecosystem; METHODOLOGIES; WATER; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology